The Differentiation Paradox of European Integration: Why Going it Alone Produces Suboptimal Results1 - Felix Biermann (JCMS: Journal of Common Market Studies, 2022)
Differentiation is not only a design feature of European integration, it is also a Member State strategy to overcome preference divergence. However, putting together an optimal group is difficult: Either the resulting club lacks the capacity to produce the club good efficiently; or differentiation attempts lead to an equally suboptimal outcome of a club too large and too heterogeneous to be effective. This paper develops an explanation of this differentiation paradox. When an avant-garde group proposes differentiation, the presence or absence of its go-it-alone power determines the outcome. The former leads to suboptimally large clubs due to the bandwagoning dynamic that produces a cascade. By contrast, the absence of go-it-alone power triggers a blockade and results in suboptimally small clubs. This actor-centred approach to differentiated integration is tested by analysing the establishment of Permanent Structured Co-operation in security and defence, which declined from an ambitious idea into a diluted reality.
Keywords: 330; European Union; differentiated integration; go-it-alone power; club theory; permanent structured co-operation